Massive elimination of multinucleated osteoclasts by eupatilin is due to dual inhibition of transcription and cytoskeletal rearrangement - Ju-Young Kim; Myeung Su Lee; Jong Min Baek; Jongtae Park; Byung-Soo Youn; Jaemin Oh (Bone Reports, 2015)
Osteoporosis is an aging-associated disease requiring better therapeutic modality. Eupatilin is a major flavonoid from Artemisia plants such as Artemisia princeps and Artemisia argyi which has been reported to possess various beneficial biological effects including anti-inflammation, anti-tumor, anti-cancer, anti-allergy, and anti-oxidation activity. Complete blockade of RANK-dependent osteoclastogenesis was accomplished upon stimulation prior to the receptor activator of nuclear factor κB (RANK)-ligand (RANKL) treatment or post-stimulation of bone marrow macrophages (BMCs) in the presence of RANKL with eupatilin. This blockade was accompanied by inhibition of rapid phosphorylation of Akt, GSK3β, ERK and IκB as well as downregulation of c-Fos and NFATc1 at protein, suggesting that transcriptional suppression is a key mechanism for anti-osteoclastogenesis. Transient reporter assays or gain of function assays confirmed that eupatilin was a potent transcriptional inhibitor in osteoclasts (OC). Surprisingly, when mature osteoclasts were cultured on bone scaffolds in the presence of eupatilin, bone resorption activity was also completely blocked by dismantling the actin rings, suggesting that another major acting site of eupatilin is cytoskeletal rearrangement. The eupatilin-treated mature osteoclasts revealed a shrunken cytoplasm and accumulation of multi-nuclei, eventually becoming fibroblast-like cells. No apoptosis occurred. Inhibition of phosphorylation of cofilin by eupatilin suggests that actin may play an important role in the morphological change of multinucleated cells (MNCs). Human OC similarly responded to eupatilin. However, eupatilin has no effects on osteoblast differentiation and shows cytotoxicity on osteoblast in the concentration of 50 μM. When eupatilin was administered to LPS-induced osteoporotic mice after manifestation of osteoporosis, it prevented bone loss. Ovariectomized (OVX) mice remarkably exhibited bone protection effects. Taken together, eupatilin is an effective versatile therapeutic intervention for osteoporosis via; 1) transcriptional suppression of c-Fos and NFATc1 of differentiating OC and 2) inhibition of actin rearrangement of pathogenic MNCs.